Essentials of inorganic materials synthesis - Rao, C. N. R. 1934-; Biswas, Kanishka (Wiley, 2015)
"Provides an introduction to inorganic materials synthesis. Covers common reactions employed in synthesis, ceramic procedures, decomposition of precursor compounds, combustion synthesis, arc and skull methods, reactions at high pressures, mechanochemical methods, use of microwaves, soft chemistry routes, topochemical reactions, intercalation chemistry, Ion-exchange methods of fluxes, sol-gel synthesis, electrochemical methods, hydro-, solvo- and iono-thermal methods, nebulized spray pyrolysis, CVD and ALD, nanomaterials, nanoparticles, nanowires, nanotubes, graphene-like layered structures, materials, metal borides, carbides and nitrides, metal oxides and chalcogenides, metal fluorides, metal silicides, phosphides, intergrowth structures, metal-rich compounds and intermetallics, superconducting compounds, and porous materials, including meal-organic frameworks"- Resumé vydavatel